2015
DOI: 10.3390/molecules200713324
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Cembranoids from the South China Sea Soft Coral Sarcophyton elegans

Abstract: Four new cembranoids, sarcophelegans A-D (1-4) and six known analogues (5-10) were isolated from the South China Sea soft coral Sarcophyton elegans. Their structures were elucidated through detailed spectroscopic analysis, and the absolute configuration of 1 was confirmed by single-crystal X-ray diffraction. The antimigratory potential of compounds 1-10 were evaluated and compounds 2 and 6 were found to inhibit human breast tumor MDA-MB-231 cell migration at 10 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 24 publications
(32 reference statements)
0
18
0
Order By: Relevance
“…827 and 1171 (Litophyton arboreum), 809 hydroperoxycembranoid 1172 (Sarcophyton trocheliophorum), 828 and 1173-1177 (Sinularia sandensis and S. exibilis). 829 X-ray studies were used to determine the complete structural and stereochemical characterization of sarcophelegan A 1164, 825 cembranoid 1173 and isosinulaexiolide K 1177. 829 X-ray studies were also used to conrm the structures and conguration of previously reported cembranoids sarsolilide B (Sarcophyton trocheliophorum) 826,830 pukalide (Leptogorgia alba) 831 and dendronpholide F (Dendronephthya sp.)…”
Section: Cnidariansmentioning
confidence: 99%
“…827 and 1171 (Litophyton arboreum), 809 hydroperoxycembranoid 1172 (Sarcophyton trocheliophorum), 828 and 1173-1177 (Sinularia sandensis and S. exibilis). 829 X-ray studies were used to determine the complete structural and stereochemical characterization of sarcophelegan A 1164, 825 cembranoid 1173 and isosinulaexiolide K 1177. 829 X-ray studies were also used to conrm the structures and conguration of previously reported cembranoids sarsolilide B (Sarcophyton trocheliophorum) 826,830 pukalide (Leptogorgia alba) 831 and dendronpholide F (Dendronephthya sp.)…”
Section: Cnidariansmentioning
confidence: 99%
“…Our previous chemical investigations on soft corals belonging to the genus Sarcophyton (Alcyoniidae), collected off the waters of the South China Sea, have obtained a series of marine natural products, including prostaglandin derivatives [1], sarsolenane-, capnosane- and cembrane-type diterpenoids [2,3,4]. These chemical components, especially cembranes, possessed various bioactivities such as anti-protozoal [5], cytotoxic [6,7], antiviral [8], and anti-inflammatory [9,10] properties, which have motivated natural product researchers to search for potential drug leads.…”
Section: Introductionmentioning
confidence: 99%
“…Cembranoids are 14-carbon cembrane ring cyclic diterpenoids ( 1 ). They are distributed primarily in the genera Nicotiana and Pinus and in some marine organisms (e.g., soft coral), in which they are thought to play a key role in survival ( 2 4 ). Cembranoids have many important bioactivities, including antimicrobial, antitumor, and neuroprotective activities ( 5 7 ).…”
Section: Genome Announcementmentioning
confidence: 99%